The Influence of Currency and Co-Creation on Customer Loyalty Mediated by Customer Satisfaction - Nurul Nashiyyah; Surya Bintari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
With the development of lifestyle education on social media, many people are finally aware of the importance of healthy living. But not many people have a lot of time to be able to keep consuming healthy food. One of the healthy instant noodles that can be used as an option is Oven Noodles. The purpose of this study was to examine the effect of Currency and Co-Creation on Customer Loyalty mediated by Customer Satisfaction on oven noodles. This research was conducted with the Bekasi Regency area as the limitation with a sample size of 110 respondents who are consumers of oven noodles. The sampling method used is nonprobability sampling with purposive sampling method. The processing used to test the correlation and regression in this study uses SmartPLS 3.2.9 which is used to test validity and reliability. In this study it can be proven 1) Currency set by oven noodle products cannot encourage the level of customer loyalty. 2) Co-Creation offered by oven noodle products cannot encourage the level of customer loyalty. 3) Customer Satisfaction felt by oven noodle consumers can encourage the level of customer loyalty.